ASSESSMENT OF PHYTOCHEMICAL CONSTITUENTS, IN VITRO ANTIMICROBIAL AND ANTIOXIDANT POTENTIAL OF ULVA EXTRACTS FROM VISHAKHAPATNAM COAST - S, Princely; Md, Dhanaraju (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Antimicrobial drug resistance is the foremost problem faced worldwide with the current antibiotic therapy in treating infectious diseases. Marine algae were considered as a potential source of biologically active compounds with antibacterial, antifungal, antiviral, and anticancer activities. Materials and Methods: In the present investigation, the purified fractions of marine algal crude extracts of different solvents such as aqueous, ethyl acetate (EtAc), and ethanol for antioxidant (1,1-diphenyl-2-picrylhydrazyl radical scavenging assay) and antimicrobial activities (agar well diffusion assay) were evaluated. Results: The extracts of EtAc, ethanol, and water showed minimum inhibitory concentration values of 3.125, 6.25, and 12.25 Î¼g/ml, respectively, for tested bacterial pathogens. The active fractions showed very little activity against Klebsiella pneumonia and Salmonella Typhi, and no activity was observed against Pseudomonas aeruginosa. The results of our screening showed that the EtAc marine algal fractions were active against some Gram-positive, Gram-negative bacteria and Candida albicans. The phytochemical analysis of aqueous, ethanolic, and EtAc extracts of marine algae showed the presence of the various phytochemical constituents such as carbohydrates, phenols, and amino acids. The ethanolic extracts showed the highest antioxidant activity as compared to aqueous and EtAc extracts. Conclusion: This work can be extended further to isolate, characterize, and discover more bioactive metabolites from marine algae, which can be exploited for the production of lead molecules in pharmaceuticals for the treatment of chronic diseases.